THE CHARACTERISTICS AND EVALUATION OF MUDFLOW FORMATION CONDITIONS IN THE TERRITORY OF NAGORNO-KHARABAKH (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
This research investigates and evaluates the factors and conditions contributing to mudflow occurrences in the Nagorno-Karabakh (NK) Region. It identifies the primary origins of mudflows and categorizes areas prone to mudflows for zoning purposes. Additionally, the study outlines current trends in mudflow evolution. Furthermore, the research proposes a range of hydraulic engineering, preventive, and forest reclamation measures aimed at mitigating mudflow risks. Implementing these measures within the NK context has the potential to yield significant and beneficial outcomes in addressing mudflow-related challenges.
Keywords: mudflow; precipitation; hydrographic network; slope and acpect of the mountains; fragmentation; weathering; climate; relief; basin; landscape